The role of cytostatic in oxidative stress reactions - Polaniak, Renata; Kwiatkowski, Aleksander; Górski, Michał; Grochowska-Niedworok, Elżbieta; Latocha, Małgorzata (Frontiers in Oncology, 2025)
Cytostatic drugs are widely applied in cancer therapy. Among the most commonly used agents are anthracyclines, such as doxorubicin, and platinum (II) complexes, including cisplatin, carboplatin, and oxaliplatin. Treatment with cytostatic drugs has been shown to enhance the mitochondrial production of reactive oxygen species (ROS). Cells regulate redox homeostasis through scavenging systems, with antioxidant enzymes playing a crucial role in neutralizing ROS. Key enzymes involved in this defense include superoxide dismutase, catalase, and glutathione S-transferase, whose activity may be modulated under oxidative stress conditions. Previous research has documented the effects of cytostatic drugs on cancer cell cultures in vitro, as well as the corresponding alterations in antioxidant enzyme activity observed under these conditions.